Tuberculosis case finding: Supplement intensified case finding among acute lower respiratory infection (ALRI) hospitalized patients in Sa Kaeo province, Thailand - Sathapana Naowarat (2020)
© 2018 Formosan Medical Association Background and purpose: We aimed to estimate TB prevalence among in-patients hospitalized with acute lower respiratory infection (ALRI) through a routine TB case finding approach (Patient-Initiated-Pathway, PIP) and among those without initial TB detection by PIP using a supplementary-Intensified-Case-Finding (supplementary-ICF) approach to determine the extent of active TB infection in patients enrolled in population-based surveillance in Sa Keao, Thailand. We also investigated secondary TB transmission through household contacts (HHCs). Methods: This was a prospective cross-sectional study. Data for hospitalized patients with ALRI were obtained from population-based pneumonia surveillance. PIP was provided in ALRI patients with suspected TB infection; those without initial suspicion of TB infection were evaluated for TB by the supplementary-ICF approach. For each active TB case finding approach, index cases were identified by acid-fast-bacillus testing and the TB prevalence was estimated. HHCs of each TB index case were followed to identify the extent of secondary TB infection. Results: TB prevalence among ALRI hospitalized patients was 12.2% among those undergoing PIP and 6.8% among those undergoing supplementary-ICF. The total number of active TB cases was doubled after implementing the supplementary-ICF method. Secondary TB infection among HHCs was 3.5 times more common for contacts of index cases identified by routine active TB case finding compared to supplementary-ICF TB. Conclusion: Supplementary-ICF among ALRI hospitalizations would be expected to result in improved active TB case detection compared to the current policy of PIP. The supplementary-ICF also enhanced early case detection and showed lower prevalence of secondary infection.